THE SOURCE REGION AND MELTING MINERALOGY OF HIGH-TITANIUM AND LOW-TITANIUM LUNAR BASALTS DEDUCED FROM LU-HF ISOTOPE DATA - A LUNAR PERSPECTIVE - Beard B.L.; Taylor L.A.; Scherer E.E.; Johnson C.M.; Snyder G.A. (My University, 1998)
Five high-Ti basalts from the Apollo 11 and 17 landing sites have been analyzed for their hafnium isotope composition. These data serve to better constrain the hafnium isotope variation of the Moon's mantle. Variations in initial εHf and εNd values of low- and high-Ti basalts imply that the source region mineral assemblages of these lunar magma types are distinct. Low-Ti basalts have higher initial εHf values, at a given εNd value, than high-Ti basalts. The differences in the hafnium and neodymium isotopic composition of low- and high-Ti basalts reflect the fact that the source of low-Ti basalts had a [Lu/Hf]n ratio approximately four times greater than its [Sm/Nd]n ratio. In contrast, the high-Ti source region had subequal [Lu/Hf]n and [Sm/Nd]n ratios. If it is assumed that mare basalts are partial melts of the Moon's cumulate mantle, the differences between low- and high-Ti basalts can only be explained by these mare magma types being generated from melting sources with distinctly different mineral assemblages. The large Lu/Hf fractionations, relative to Sm/Nd fractionations, of low-Ti basalts can best be produced by an assemblage of olivine and orthopyroxene with trace amount of clinopyroxene that crystallized early in the history of the Lunar Magma Ocean (LMO). The subequal [Lu/Hf]n and [Sm/Nd]n fractionations of high-Ti basalts can be produced from a variety of ilmenite-bearing mineral assemblages.Low- and high-Ti basalts have similar Lu/Hf ratios, approximately 0.6 times chondrite. The low Lu/Hf ratios measured for these mare magmas contrast sharply with the high Lu/Hf ratios (greater than chondritic) calculated for their sources from initial εHf values and an assumed chondritic bulk moon initial εHf value. The difference between the measured Lu/Hf of a lava, vs. the calculated Lu/Hf of its source, implies that during partial melting, Lu was preferentially retained in the residual source, relative to Hf. In order to explain the extreme fractionation of measured Lu/Hf ratios we suggest mare basalts can best be explained using a polybaric melting model. Initial melting of a garnet bearing source followed by continued melting in the spinel stability field can produce the required Lu/Hf fractionations and produce a liquid that last equilibrated with a residuum of olivine and orthopyroxene.